Inorganic Solid‐State Electrolytes for Solid‐State Sodium Batteries: Electrolyte Design and Interfacial Challenges - Dongsoo Lee; Ashok Kumar Kakarla; Seho Sun; Patrick Joohyun Kim; Junghyun Choi (ChemElectroChem)
Abstract Recent advancements in inorganic solid electrolytes (ISEs), achieving sodium (Na)‐ion conductivities exceeding 10 ‐2 S cm‐1 at room temperature (RT), have generated significant interest in the development of solid‐state sodium batteries (SSSBs). However, the ISEs face challenges such as their limited electrochemical stability windows (ESWs) and compatibility issues with high‐capacity, high‐voltage cathode materials and Na metal anodes. The success of high‐performance SSSBs hinges on developing ideal ISEs that deliver high Na+ ion conductivities, robust chemical and electrochemical stability, and well constructed electrode/ISE interfaces. This review explores the fundamental principles and strategies to optimize SSSB performance by addressing issues related to ISEs and their interfaces, emphasizing that many interfacial challenges are intrinsically linked to ISE properties. It highlights recent advancements in ISE research, including the mechanisms of Na‐ion conduction and the key factors influencing it, such as crystal structure, lattice dynamics, point defects, and grain boundaries. It also discusses prototyping strategies for cell design from the perspectives of material and defect chemistry. Additionally, the review identifies key challenges and future opportunities for advancing SSSBs and provides rational solutions to guide future research toward the practical realization of high‐performance SSSBs. Keywords: Solid‐state sodium batteries; Inorganic solid electrolytes; Interfacial mechanism; Electrochemical stability window; Ionic conductivity; Modification strategies